Factors That Affect Unemployment Among Graduates - K. Hemanth Kumar,; Salahudin, Shahrul Nizam (Research in Management of Technology and Business, 2023)
The problem of graduate unemployment in Malaysia has been a major source of public concern. Malaysian universities, public or private, produce a large number of graduates each year, yet a surprisingly low percentage get employed. This study aimed to determine the relationship between the factors that affect unemployment and unemployment among graduates. This research sent a web survey through social media apps such as WhatsApp. The population of this investigation is 3190 graduates of UTHM. The test measure for this investigation is 341 graduates sample size. 250 graduates took part and reaction to the inquiry. Quantitative approaches center on this consideration, and the test collect based on the test who replies to the surveys. The responses were analyzed by mean of frequency distribution, mean and standard deviation analysis by using Statistical Package for the Social Science (SPSS) software. Communication skills, know-how, job mismatch, and employability skills affect unemployment. The study indicated that communication skill, know-how, job mismatch, and employability skills positively correlate with unemployment. This research might help graduates get jobs and supervisors prevent problems early. Future studies should seek a bigger sample size and include all Malaysian states to acquire more accurate and dependable results, according to this study.